Early-Life Intervention Using Exogenous Fecal Microbiota Alleviates Gut Injury and Reduce Inflammation Caused by Weaning Stress in Piglets - Ma, Xin; Zhang, Yuchen; Xu, Tingting; Qian, Mengqi; Yang, Zhiren; Zhan, Xiuan; Han, Xinyan (Frontiers in Microbiology, 2021)
Fecal microbiota transplantation (FMT) could shape the structure of intestinal microbiota in animals. This study was conducted to explore what changes happen in the structure and function of microbiota caused by weaning stress, and whether early-life FMT could alleviate weaning stress through modifying intestinal microbiota in weaned piglets. Diarrheal (D) and healthy (H) weaned piglets were observed, and in the same farm, a total of nine litters newborn piglets were randomly allocated to three groups: sucking normally (S), weaned at 21d (W), and early-life FMT + weaned at 21d (FW). The results demonstrated that differences of fecal microbiota existed in group D and H. Early-life FMT significantly decreased diarrhea incidence of weaned piglets. Intestinal morphology and integrity were improved in FW group. Both of ZO-1 and Occludin (tight junction proteins) of jejunum were greatly enhanced, while the Zonulin expression was significantly down-regulated through early-life FMT. The expression of IL-6 and TNF-α (intestinal mucosal inflammatory cytokines) were down-regulated, while IL-10 (anti-inflammatory cytokines) was up-regulated by early-life FMT. In addition, early-life FMT increased the variety of intestinal microbial population and the relative amounts of some beneficial germs such as Spirochaetes, Akkermansiag and Alistipes. Functional alteration of the intestinal microbiota revealed that lipid biosynthesis and aminoacyl-tRNA biosynthesis were enriched in FW group. These findings suggested that alteration of the microbiota network caused by weaning stress induced diarrhea, early-life FMT alleviated weaning stress in piglets, which was characterized by decreased diarrhea incidence, improved intestinal morphology, reduced intestinal inflammation and modified intestinal bacterial composition and function.